The Influence of the Progressive Section Method on Single Art Movements in Beginner Athletes - Rizal Dwi Permana; Muhammad Nur Alif; Anggi Setia Lengkana (Universitas Negeri Semarang, 2026)
The single art of pencak silat is a competitive category with extremely intricate motions that require exacting skill, steady pace, and simultaneous comprehension of movement. Due to their lack of coordination and expertise, new athletes frequently find it challenging to properly comprehend and grasp the movement sequences. This circumstance emphasizes the necessity of training techniques that can deconstruct intricate movement patterns through organized and methodical learning phases. This study aims to measure the efficiency of the progressive section method on the movement skills of standard single arts for beginner IPSI pencak silat athletes in Cilacap Regency. Standard single arts have a high level of movement complexity, thus requiring a gradual and structured learning approach. This study implemented an experimental design with a one-group pretest–posttest model. The research sample consisted of 12 beginner athletes selected using a saturated sampling method. The research instrument was a standard single arts assessment format according to the PB IPSI guidelines, while data analysis used normality tests and t-tests. The results showed an increase in the average score from pretest to posttest as well as a significant difference between before and after treatment. This indicates that the progressive section method successfully improves the movement skills of standard single arts techniques of beginner athletes. This method facilitates athletes to recognize step-by-step movements, improve technical accuracy, and maintain consistent movement rhythm. Therefore, the progressive section method is recommended as a training technique in the development of beginner pencak silat athletes.